EL ORDOVÍCICO DE LA REGIÓN DEL CERRO BOLA EN EL BLOQUE DE SAN RAFAEL, MENDOZA: SUS FAUNAS GRAPTOLÍTICAS (Ameghiniana, 2014)
Recent research canied out in the pre-Carboniferous sequences on the San Rafael block allowed the recognition of the following three regional facial types: l. Cerro Bola-Arroyo Pavón facies (Pavón Formation, nom. subst.i, characterized by massive sandstones, siltstones and shales; 2. Rio Seco de los Castaños facies (Rio Seco de los Castaños Formation) made up of typical turbidite cycles and 3. Rio Diamante facies (Horqueta Formation) greenschists of epimetamorphic origino A rich graptolite fauna composed of 23 taxa (families Glossograptidae, Nemagraptidae, Dicranograptidae, Diplograptidae, Orthograptidae, Lasiograptidae and Retiolitidae) has been found in the cerro Bola-arroyo Pavón facies. From base to top the graptolites are arranged into three distinctive assemblages as follows: l. Lasiograptus costatus Lapworth, Normalograptus cf. tubuliferus Lapworth, Amplexograptus aff. arctus Elles and Wood, Orthoretiolites sp., Climacograptus bicornis Hall and Climacograptus tridentatus Lapworth; 2. Dicranograptus ramosus ramosus Hall, Dicranograptus nicholsoni nicholsoni Hopkinson, Dicranograptus ramosus cf. longicaulis Hall; 3. Orthograptus truncatus aff. truncatus (Lapworth), Orthograptus aff. apiculatus Elles and Wood, Climacograptus bicornisHall, C. tridentatus Lapworth, Pseudoclimacograptus scharenbergi Lapworth, Glossograptus aff. ciliatus Emmons, Crypograptus insectiformis Ruedemann, Leptograptus validus validus Elles and Wood, Normalograptus ef. tubuliferus Lapworth, Dicellograptus salopiensis Elles and Wood, D. forchammeri ci.flexuosus Lapworth, Orthoretiograptus sp., Hallograptus sp., and Gtypograptus sp. The speeies of C. bicornis and C. tridentatus are present only in the lower and upper graptolite assemblages. The graptolites are described and their biostratigraphic ranges discussed. The age of the sequenee is Lower Caradocian (c. bicornis Biozone).